OPTIMALISASI MANAJEMEN BANDWIDTH JARINGAN LOCAL AREA NETWORK PADA SEKOLAH MENENGAH PERTAMA TARUNA BHAKTI DEPOK - Muhammad Andika Saputra; Octo Bagas Wicaksono (LPPM Nusa Mandiri, 2018)
Good bandwidth management will maximize the smooth use of the internet for users. However, bandwidth management in the internet network at Taruna Bhakti Junior High School has not been used optimally in meeting the needs of users, where when users increase internet access, the connection will be slow. Besides that, in the Taruna Bhakti Middle School in terms of security on the router device, it is still not optimal due to the prevention of hacking attacks. Based on the results of the analysis, it can be concluded that some of the problems that occur at the Taruna Bhakti Depok Junior High School include among them several client personal computers (PCs) whose connection speed is slow due to uneven distribution of bandwidth, absorbed a lot of bandwidth on hotspot users when downloading using torrent or Internet Download Manager (IDM) which can slow down other users' internet connections, and Lack of security on routers at Taruna Bhakti Junior High School where there are still many weaknesses such as vulnerability to hacking by hackers, and the spread of viruses on computer networks. The purpose of this paper is to analyze and understand the configuration of the Local Area Network network at Taruna Bhakti Junior High School, to find out what can be done to improve network quality at Taruna Bhakti Junior High School and find out what can be done to optimize bandwidth usage at Taruna Bhakti Junior High School.